Application of cast parts in mechanical engineering - M. A. Sadokha; A. A. Andrushevich (Литьë и металлургия, 2022)
Information about the volumes of castings production in various countries of the world is given. The situation with the castings production in the Republic of Belarus is considered in more detail. An outlook on the ways of further foundry production development is presented. Recommendations have been developed on the main areas of application of cast products in mechanical engineering.